The Effect of Employee Engagement on Employee Performance with Organizational Commitment as Intervening Variable and Percieved Organization Support as a Moderating Variable at The Regional Secretariat of Bireuen District - Aiyub Aiyub; Em Yusuf; Raja Bintan; Adnan Adnan; Azhar Azhar (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
Employee performance is an important issue that is often discussed in various scientific literatures, but many organizational leaders do not know clearly about the benefits of performance and the factors that influence it. This study aims to determine the effect of employee engagement, organizational commitment and perceived organization support on employee performance through mediation and moderation effects. The data used are primary data obtained through distributing questionnaires to 120 employees who work at the Regional Secretariat of Bireuen Regency. This study uses the Structural Equation Model-Partial Last Square (SEM-PLS) model by using the Smart-PLS device. The results of the study found that direct employee engagement has a positive and significant effect on organizational commitment. Furthermore, direct employee engagement and organizational commitment were found to have a positive and significant effect on employee performance. Indirectly found that organizational commitment mediates the effect of employee engagement on employee performance. The results of this study also found that perceived organization support moderated negatively (weakened) the effect of employee engagement on employee performance. Based on the results of the study, it is suggested to the leadership of the Regional Secretariat of Bireuen Regency to be able to provide full support to employees in carrying out employee work, especially in order to increase employee engagement and organizational commitment and perceptions of employee support for their organization.